Sistem Pakar Identifikasi Defisiensi Unsur Hara Pada Tanaman Kopi Menggunakan Metode Certainty Factor Berbasis Web - Eka, Muhammad; Anggraini, Novita (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2017)
As the third largest coffee producing country in the world after Brazil and Vietnam, Indonesia is able to produce at least 748 thousand tons or 6.6% of coffee production in 2012. Of this amount, Robusta coffee production reached more than 601 thousand tons (80.4% ) and arabica coffee production reached more than 147 thousand tons (19.6%) .The area of coffee plantation in Indonesia reaches 1.3 million hectares (ha) with Robusta coffee plantation area reaches 1 million ha and arabica coffee plantation area reaches 0 , 30 ha. The use of technology in the cultivation of coffee cultivation in Indonesia, especially smallholder plantations is still minimal technology. Expert system approach by using certainty factor method to overcome uncertainty in identifying nutrient deficiency in coffee plant try to give solution that can be used by coffee farmer especially in smallholder plantation in sidical area of karo regency of north sumatera. By doing a direct observation of the leaves of coffee plants and ensure the symptoms of nutrient deficiency what actually happens in the coffee plant it is with this expert system of certainty of nutrient deficiencies can be known in detail without having to consult directly to the expert. Thus the fertilization process can be done properly, so it will affect the cost of production to a minimum.